2013
DOI: 10.1177/1538192713475453
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Cultural Validity of a College Student Engagement Survey for Latinos

Abstract: Using critical race theory and quantitative criticalist stance, this study examines the construct validity of an engagement survey, Student Experiences in the Research University (SERU) for Latino college students through exploratory factor analysis. Results support the principal seven-factor SERU model. However subfactors exhibited differential structure patterns suggesting sense of agency, initiative-taking, self-competency, and self-efficacy as a means of reflecting potential cultural nuances relative to La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Students may be the best qualified to describe what they have gained from their experience in a university, particularly in some areas such as affective outcomes and practical skills [44]. However, for better results, items should be clearly worded and students have the information required to accurately answer the questions within the prevailing conditions [10]. Research shows that students respond more carefully and with much personal interest to the content of such questionnaires [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students may be the best qualified to describe what they have gained from their experience in a university, particularly in some areas such as affective outcomes and practical skills [44]. However, for better results, items should be clearly worded and students have the information required to accurately answer the questions within the prevailing conditions [10]. Research shows that students respond more carefully and with much personal interest to the content of such questionnaires [43].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that suggests structural modification for the student engagement scale when used in a single institution study as opposed to large scale study [7][8][9]. Regardless of this, however, in higher education research, development and validation of student engagement and self-reported gains scales and cross-cultural comparisons have been rarely studied [10]. The lack of evidence supporting the cultural validity of constructs such as self-reported gain has implications for the wider utilization of those educational constructs across different higher education systems allowing customization to fit with different circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the continued increase in Latinos enrolling in higher education, Latinos have enrolled in a disproportionately small number of institutions of higher education throughout the United States (Cook, Pérusse, & Rojas, 2012; de los Santos & Cuamea, 2010; Galdeano et al, 2012; Zarate & Burciaga, 2010). Attainment gaps for Latinos continue to persist despite increases in enrollment, changes in public policy, and institutional efforts to serve Latinos (Aguayo, Herman, Ojeda, & Flores, 2011; Crisp & Nora, 2010; Galdeano et al, 2012; Hernandez et al, 2013; Zarate & Burciaga, 2010).…”
Section: Institutional Characteristicsmentioning
confidence: 99%
“…First-generation students are defined as students who are immigrants and whose parents did not attend college (Boden, 2011; Carolan-Silva & Reyes, 2013; Pino et al, 2012). Many first-generation Latinos often lack the social and academic capital necessary for academic success, often making their navigation of the academic environment challenging (Case & Hernandez, 2013; Crisp & Nora, 2010; Hernandez et al, 2013; Pino et al, 2012).…”
Section: Institutional Characteristicsmentioning
confidence: 99%
“…Fall 2011 was a significant time for me. Two events influenced my thinking about a research project that I was developing alongside Michael Mobley that used Student Experience in the Research University (SERU) survey data on college student engagement (Hernández, Mobley, Coryell, Yu, & Martinez, ). The first was my attendance at the Alexander McQueen exhibit at the Metropolitan Museum of Art.…”
mentioning
confidence: 99%